ONLINE DA’WAH (ISLAMIC MISSIONARY WORK) MODEL (A Study on the Use of the Internet as Missionary Media by Muballigh/Muballighah of UIN Alauddin) - Akil, Muhammad Anshar (Journal of Islam and Science, 2015)
This study analyzes the online missionary activity models for muballigh-muballighah (male and female Muslim preachers - lecturers and employees) at UIN Alauddin Makassar. The purposes of this research are: (1) to describe the use of online missionary media for the muballigh- muballighah at UIN Alauddin; (2) to clarify the supporting factors and obstacles to the use of online media by the muballigh/muballighah at UIN Alauddin; and (3) to formulate the model of online missionary media for muballigh- muballighah at UIN Alauddin Makassar. The study implements a qualitative approach to issues examined. A qualitative research is a method to explore and understand the meaning emerging from social problems. This is a phenomenological research implemented to describe phenomena or occurrences universally experienced by the objects under study. The results indicate that: the muballigh-muballighah at UIN Alauddin utilize online media in the forms of: (1) web site; (2) web blog; (3) social media facebook; and (4) twitter. Those kinds of media are dominantly used to convey the message of education, personal experience, motivation, or inspiration. Religious messages are still rarely presented either in textual or contextual manner through the online media used by lecturers and employees of UIN Alauddin Makassar. Supporting factors for the implementation of online missionary activity are: (1) online media have become a necessity for the muballigh-muballighah living in this era; (2) the availability of internet facilities, including good hardware, software, and networks; and (3) online media facilitate easy JOURNAL OF ISLAM AND SCIENCE 73 Volume 02 Number 01, JUNE 2015 Online Da’wah.... Muhammad Anshar Akil communication. The inhibiting factors comprise: (1) limited facilities owned; (2) lack of skills in using the internet; (3) loads of activities as lecturers and employees at UIN Alauddin Makassar. The online missionary activity models consist of seven components: (a) the communicators are Lecturers and Employees UIN Alauddin Makassar; (b) the media include web site, web blogs, facebook and twitter; (c) the messages delivered are of religious, personal, social, and universal themes; (d) the communicants are students and general public; (e) the feedback is positive; (f) the supporting factors involve the need, facilities, easiness of using online media; and (g) the inhibiting factors comprise limited facilities, lack of skills, and loads of activities as lecturers and employees of UIN Alauddin Makassar.